FINANCIAL DISTRESS ANALYSIS OF INDONESIA RETAIL COMPANIES - Yelli Yulian; Idqan Fahmi; Tanti Novianti (Journal of Management and Business Review, 2020)
Retail industry is an industry whose business activities provide products in the form of goods and or services to individuals, themselves, families or households. In the past few years there have been many closures of retail outlets in Indonesia. In 2016 in global retail development, it was noted that Indonesia was included in the 5 most active retail countries as well as being among the 5 countries with the biggest sales in Asia. In recent years there have been many closures of retail outlets in Indonesia. The current retail condition in Indonesia faces many problems, one of which is the distortion of new income, namely retail that has no place or so-called electronic commerce (e-commerce). E-commerce involves buying and selling products (such as physical goods, digital products or services) that are transacted through computer networks.This study uses data from 23 companies to describe the condition of the retail business in Indonesia. Data collected from 2013 to 2017 and analyzed using panel data regression with three approaches Altman, Springate and Zmijewski. All companies experienced a decline in financial performance. The factors that influence the condition of financial distress are net profit margin, current ratio, size of firm and total asset turn over.